Education as a key strategy of postmodern philosophy: overcoming the trauma of non‐freedom - Tytar, Olena Volodmyrivna; Havryliuk, Yurii Romanovych (Харківський національний університет імені В. Н. Каразіна, 2021)
The formation of personality attracted the attention of both classics of philosophical thought, in particular the works of C. Pierce, Z. Freud, and representatives of modern philosophical discourse (Z. Bauman, P. Ricceur, J. Hararri, K. Wilber). Recent research states that the main obstacle to formation of the individual and society is cultural trauma that arises as a result of the development of totalitarian colonial societies in the twentieth century. The concept of cultural trauma is analyzed in the studies of J. Alexander, С. Сaruth , A. Neаl. The aim is to explore the individual in modern and postmodern paradigm, the application of concepts of development, education, self‐development and self‐education of the individual in postmodern discourse, to consider education and self‐development as key strategies of postmodern philosophy in overcoming totalitarian cultural trauma. Scientific novelty. It is stated that education, development and self‐development of the individual become main strategies of information age and postmodern culture, which contributes to overcoming the totalitarian colonial traumatic experience. The personality in modern and postmodern paradigm (concepts, attitude to the personality, processes of education, social institutions, self‐education) is investigated. It should be noted that self‐development of the individual will acquire a global scale: whether it is measured by the coefficient of happiness or economic efficiency of a society, there are scientific debates, one thing is certain ‐ at the same time education, self‐education and upbringing become the deal of not individual countries, but humanity on the whole. Conclusions. 1. In the modern paradigm, the individual implicitly contains the antithesis of mental and physical origin, immutability, and hence eternity, and development as a certain adaptation of man to external circumstances of socio‐cultural life. 2. Postmodernism replaces this contradiction with the controversy or dialectic of personality as unchanging, perfect and at the same time constantly growing under the influence of both external and internal factors, the application of the concepts of self‐development and self‐education philosophical paradigm, as modern and colonial discourse seeks to do. 3. Based on the presented argumentation, the conclusion is made about education and self‐development as key strategies of postmodern philosophy in overcoming totalitarian cultural trauma of imprisonment.

Становлення особистості привертало увагу як класиків філософської думки, зокрема це праці Ч. Пірса, З. Фрейда, так і представників новітнього філософського дискурсу (З. Бауман, П. Рікер, Ю. Хараррі, К. Уїлбер). У дослідженнях останнього часу говориться, що головною перепоною у становленні особистості та суспільства є культурна травма, яка виникає як наслідок розвитку тоталітарних колоніальних суспільств у ХХ столітті. Поняття культурної травми аналізується у дослідженнях Дж. Александера, К. Карут, А. Ніла. Мета – дослідити особистість у модерній та постмодерній парадигмі, застосування понять розвитку, освіти, саморозвитку та самоосвіти особистості в постмодерному дискурсі, розглянути освіту та саморозвиток як ключові стратегії філософії постмодерну у доланні тоталітарної культурної травми несвободи. Наукова новизна. Констатується, що освіта, розвиток та саморозвиток особистості стають основними стратегіями інформаційної доби і постмодерної культури, що сприяє подоланню тоталітарного колоніального травматичного досвіду. Досліджено особистість у модерній та постмодерній парадигмі (поняття, ставлення до особистості, процесів виховання, соціальних інститутів, самоосвіти). Можна відмітити, що саморозвиток особистості придбає глобальний масштаб: чи буде він вимірюватись коефіцієнтом щастя чи економічною ефективністю того чи іншого суспільства, ідуть наукові суперечки, беззаперечно одне – одночасно освіта, самоосвіта і виховання стають справою не окремих країн, а людства загалом. Висновки. 1. У модерній парадигмі особистість імпліцитно містить антитезу душевного та тілесного начала, незмінності, а отже вічності, та розвитку як певної адаптації людини до зовнішніх обставин соціально‐культурного буття. 2. Постмодерн замінює це протиріччя контроверзою або діалектикою особистості як незмінної, довершеної і одночасно постійно зростаючою під впливом як зовнішніх, так і внутрішніх факторів, застосування понять саморозвитку та самоосвіти особистості сприяє діалектичному розумінню самої особистості, що поліфункціональна і не може бути вписана лише в одну філософську парадигму, як прагне це зробити модерн та колоніальний дискурс. 3. На основі представленої аргументації зроблено висновок щодо освіти та саморозвитку як ключових стратегій філософії постмодерну у доланні тоталітарної культурної травми несвободи.
Освіта як ключова стратегія філософії постмодерну: долання травми несвободи
Keywords: personality; education; philosophy of culture; philosophical anthroropology; postmodern; cultural trauma; philosophy of education; freedom; особистість; освіта; філософія культури; філософська антропологія; постмодерн; культурна травма; філософія освіти; свобода